A constituição da paternidade na maternidade adolescente - Guimarães, Marianna Ribeiro (2019)
The conception of paternity has undergone historical and cultural changes; the social transformations and the construction of a family feeling have transformed the idea of a father with the passage of time. In contemporary times, the father hás been gaining prominence in the development of the baby, the family and in the experiences of the being fathered, marked mainly by the diversity of experiences. With regard to adolescent pregnancy, a consolidated field of research and with several contributions to Psychology, there is a gap regarding studies on paternity, especially in the clipping of the parents of the babies of adolescents who are pregnant. Thus, this work has a general objective to understand and analyze the process of development of the fatherhood of the parents of the babies of pregnant adolescents. In addition, as specific objectives, identify and analyze the socioeconomic, family and school contexts of parents, as well as understand the relationships between fatherbaby, mother-baby, father-mother-baby. It inserted in the larger project entitled Empowering professionals, children, and adolescents of a coastal community of Maceió; the Research Ethics Committee of the responsible institution approved this work. This a qualitative research and the following instruments applied during the prenatal period: socioeconomic profile characterization form; semi-structured interviews, Drawing Procedure of Families and Stories. This last instrument consists in the application and interpretation of a series of drawings made by the participant (drawing of any family, drawing of a family that would like to have, drawing a family in which someone is not well and the drawing of the family itself). This allows an in-depth understanding of family dynamics and parenting in the family relationship. For this research, five parents of babies of pregnant adolescents Who underwent prenatal care in Basic Health Units in the municipality of Maceió participated, with ages between 20 and 43 years, with a level of schooling that varied between elementary and high school. To meet the ethical precepts in research, participants completed and signed the Informed Consent Term (TCLE). The interviews recorded and transcribed to analyze thedata collected. The data analysis based on the content of the interviews, also contemplating the nonverbal expressions observed by the researcher, as well as supported in the psychoanalytic theory of Winnicott. Procedure for Drawing Families with Stories analyzed according to Trinca and Brito (2013) recommendations. It observed with this work that parenting has been more participatory and that financial maintenance is still a concern of the parents. Relations with the families of origin are present in the understanding of paternity of the interviewees. The imaginary baby also brings in the desires of the parents, physically and in situations in which the parents wish to live with their children. Gestation been accompanied by parents by offering emotional support to their mothers. However, prenatal care still hás little parental involvement, which has to reconcile work with paternity. Thus, it is possible to conclude that parents have created, in a particular way, caring relationships with pregnant women and their babies. However, they still consider the birth of babies as a marker of the feeling of fatherhood.